Pengenalan Peran Radiografer Menangani COVID-19 di Rumah Sakit kepada Siswa/i Sekolah Menengah Atas - T.Mohd Yoshandi; Shelly Angella; R. Sri Ayu Indrapuri; Aulia Annisa; Marido Bisra; Annisa; Devi Purnamasari; Danil Hulmansyah (LPPM Universitas Awal Bros, 2021)
In 2020 WHO gave the status that Corona Virus Disease -19 (COVID-19) became a Global Pandemic. Health workers who handle cases of COVID-19 are responsible for protecting themselves and others to break the chain of spread of COVID-19. One of the medical personnel involved in handling COVID-19 is a radiographer. The role of radiographers in handling COVID-19 in hospitals needs to be socialized more, considering its very important role in evaluating patient health and requiring radiographers to have direct contact with positive patients. For radiographers, the source of danger at work is not only COVID-19, but ionizing radiation is also a source of danger that must also be taken into account. The public must also be aware of the risks and challenges faced by radiographers in their work during this pandemic. The method used in this community service is by presentation or extension or education. This Community Service is carried out to introduce the role of radiographers in hospitals when there are patients with COVID-19 cases, so that these health workers can be more recognized by the general public. The target audience for this community service is SMA (High School) students with the aim of cultivating an interest in the younger generation to become radiographic health workers. As a result of this community service, participants were given knowledge about radiology, starting from workers (radiographers), the tools used to their role in the health world. The results of participants' understanding of Community Service activities, all participants understood the role of radiographers in treating COVID-19 patients in hospitals and 91% of participants understood what a radiographer was, and as many as 64% of participants were interested in becoming radiographers, and the remaining 36% of participants were not interested. be a radiographer. Community service activities regarding the role of radiographers in hospitals have been carried out well. Participants become more familiar with the duties of workers in the radiation field.